An Integrated Approach in COVID-19 Patient with High Oxygen Dependency Status - Satyal, Jaya; khatiwada, Kasi; koju, Pratigya; Adhikari, Jhularam; kc, Pradeep (Annapurna Journal of Health Sciences, 2023)
Covid-19 has become a global pandemic leading towards thousands of death worldwide.It is infectious disease caused by a new corona virus called SARS-cov-2. WHO learned of the new virus on 31 december 2019 for the first time, following a report of cluster of cases of viral pneumonia in Wuhan, China. However, we report a presentation of covid infection in a 45 year old male in a covid hospital where he was treated with integrated approach i.e Allopathy,Ayurveda,TCM(Trad itional Chinese Medicine),Yoga and physiotherapy.During treatment Patient was kept on cpap for some days and got discharged after complete treatment.